Moral and cultural discourses surrounding women athletes in Egypt - El-Ghazaly, Yasmeen (AUC Knowledge Fountain, 2018)
Choosing my thesis topic and title was both no easy task; yet came naturally to me. My thesis titled, “Moral and cultural discourses surrounding women athletes in Egypt” discusses the effects of social spaces, notions of femininities, masculinities, and gendered power relations, social and cultural stigmas surrounding Egyptian women athletes through exploring the daily challenges of a selection of amateur and professional women athletes residing in Egypt as they embark on changing the various social stigmas, stereotypes and limitations facing them in the everydayness of their lives in Egypt as athletic women. The thesis argues that the interplay of the heavily gendered social structure in Egypt along with the patriarchal and cultural conformities defining gender roles in our society significantly affect the everyday lives of Egyptian women athletes. Choosing sports as a means of investigating how culture, religion, state politics and gender stratification intervene with women’s lives and their accessibility to the public spheres emphasizing how their bodies are gendered in Egypt came very naturally to me. I come from a fairly athletic family; both my parents as well as my brother still maintain an athletic lifestyle on a daily basis. Sports to me represents a plethora of values, it is a means of releasing stress, of having fun, of feeling alive and of course of maintaining a healthy long happy life. By far one of my biggest fears is to be forced to stop playing sports or having limited options in what kind of sports I would be able to pursue for any reason at all. Surely enough in my early twenties and due to my poor choice for a spouse, despite being in perfect health conditions, I was banned by my now ex-husband to play any sort of sports ‘publicly’. The only thing I was allowed to do was to either join a closed ladies-only aerobics class or walk on a treadmill in baggy clothes, not even in the street. After regularly playing tennis, squash, cycling and martial arts for as long as I can remember, this seemed alien and absurd to me, yet due to my fairly young age and inexperience, I obeyed his orders hoping to pacify the male insecurities in him thinking that it was his ‘right’ as a husband. This attitude was certainly fortified by the social, cultural and religious rhetoric surrounding me at the time. It is without doubt that after abandoning sports for the entire duration of my relationship with that abusive person, which was over 10 years, I felt my own personality wilt away and my identity collapse faster than I could even try to remedy at any point. I was just an empty soulless shell of myself. Needless to say, the first thing I pursued with a vengeance after my divorce was sports. This negative marriage only fuelled me along with my ever-supportive current husband Mohamed to explore the depth of why and how sports can be an issue for many women in Egypt. The multiple social, cultural and religious discourses and interpretations surrounding this topic was the main essence where I based my fieldwork among my interlocutors aiming to unravel the intricacies within the accessibility and acceptability of being an athletic woman in Egypt. As with any academic research I needed to look for several reliable sources discussing women and sports in Egypt, although Egypt has positively come a long way in this domain, I did not find much research on the topic per se. As challenging as this made my research, but it also meant that researches like mine will hopefully add more value to this topic in the future for other researchers to perhaps build further work upon. Furthermore, the executed fieldwork showed how inconsistent interpretations and perspectives both men and women had about this topic were regarding the interplay of culture laced with religious references in Egypt despite affiliating to certain supposedly well-educated and slightly westernized social classes. My research also aimed at spreading more awareness about the role and impact of sports on women’s lives in Egypt analyzing the restrictions women who choose this lifestyle could be faced with that may interfere with reaching their athletic goals. Choosing to observe and try out different gyms myself in different residential areas in Cairo as well as conducting interviews with a diverse span of interlocutors from acquaintances to friends to complete strangers interested in the topic gave me confidence in the input I had contributing to the essence of this research. It is worth noting that as I advertised for the need of interviewing interested interlocutors, I had no idea that I would receive over 100 interview requests from people of different classes, different backgrounds some who were total strangers to me and not everyone was athletic. The diversity gave me rich field notes to work with in my research. Conceptually, when discussing the multiple discourses of women athletes in Egypt, seeing how space is defined, limited at times and gendered make a significant impact on the perceptions of their accessibility and development in the social spaces around them. Henri Lefebvre says that social space is a social product, or a complex social which affects spatial practices and perceptions. Combining LeFebvre’s work on social spaces and Daphne Spain’s work on gendered spaces talking about the gender stratification and how this has progressed and regressed within different eras and countries relates much to what limits women’s accessibility in the public spaces in Egypt. Space is everything; it determines who we are as humans. As a woman living in Egypt, seeing how space defines my existence as well as my life choices, this concept relates completely to the topic at hand. Going to Spain's work, "gendered spaces" in homes, schools, and workplaces reinforce and reproduce dominant status divisions that are taken for granted. Women's position within society, whether measured as power, prestige, economic position, or social rank, is related to spatial segregation insofar as existing physical arrangements facilitate or inhibit the exchange of knowledge between those with greater and those with lesser status. These broad concepts among others outlined the mainframe of my fieldwork and research tools. Among my fieldwork finding was two very distinctive interviews that are of relevance to highlight in this presentation. Against the developmental discourses, which I personally stand critical of, I interviewed an uneducated cleaning lady who although apparently comes from a less fortunate working class yet was adamant on training both daughters martial arts to invade the public spaces with confidence to be able to face the aggression and hostility they usually encounter within their social circles. On the other hand, I had an interview with an upper class AUC Professor who although is an avid athlete himself with ample western exposure and is well respected among his colleagues here, firmly believes that women are empowered through their domestic roles and not through invading the public spaces. Prior to doing my fieldwork, as a researcher, I had my own prejudgments and deliberations that were swiftly ripped apart as I progressed through with this thesis. In my point of view, this research has succeeded in accomplishing its main purposes, it shed the light on the intersections of how patriarchy, public spaces accessibility and acceptability politics as well as the effect on women’s bodies limiting their access to sports came together, however the main accomplishment for me personally, was the opportunity to share as a woman athlete myself, our collective narratives on how our bodies are perceived and our restricted mobility is represented with our passion for sports bringing us together as we negotiate our accessibility to public spaces and the sports arena in Egypt. This thesis looks at the effects of social spaces, femininities, masculinities, and gendered power relations surrounding Egyptian women athletes through exploring the daily challenges of a selection of amateur and professional women athletes residing in Egypt as they embark on changing the various social stigmas, stereotypes and limitations facing them in the everydayness of their lives in Egypt as athletic women. Neither patriarchal notions, nor interpretations of Islam are static, consistent nor are they monolithic entities. However throughout this thesis what is meant by both terms will be highlighted in relevance to the repercussions with respect to my interlocutors’ experiences. The thesis argues that the interplay of the heavily gendered social structure in Egypt along with the patriarchal and cultural conformities defining gender roles in our society significantly affect the everyday lives of Egyptian women athletes. The analysis and fieldwork executed in this research aim to uncover the notions surrounding what defines femininity and masculinity in the lives of these women. Looking at the pre-existing gender roles assigned to women in Egypt across different social levels in addition to the various social conformities and ideologies embracing our society that heavily stem from a myriad of cultures, traditions and religious beliefs inherently affect how athletic women lead their lives in Egypt. My fieldwork revealed how these women chose to defy years of social stigmas and different cultural mindsets laced with religious predispositions not necessarily on par with the level of exposure needed to lead and maintain an athletic lifestyle in Egypt. My analysis will be founded on broader concepts of the understandings and interpretations of social spaces, gendered bodies, power-gender relationships and discourses of patriarchy and masculinity complexes governing women’s lives as they choose to incorporate sports into their lives whether professionally or not.